The Mechanism of Formation of Structural Heterogeneitics in Polyaniline - Hakhnazaryan, T.L.; Matnishyan, H.A. (Journal of Composites and Biodegradable Polymers, 2014)
The regularities of polyaniline formation, the influence of various additions, conditions of synthesis of the main and intermediate, including hydrolysis, products on the structure of obtained materials are studied. Making use kinetic and thermochemical methods the mechanisms of polycondensation by N-phenyl-1,4-benzoquinonodiimine, initiation macromolecules growth as result of anilines addition to electrophile quinonoimine groups of the polymer are confirmed. The chemical aspects of reactions leading to formation of structural heterogeneitics, branchings, breaching of effective conjugation, termination and sewing together of chains are analyzed.